Causes of Financial FDI Inflows into Sub‐Saharan Africa (SSA): Evidence from Ghana. (12th June 2014) - Adams, Kweku; Debrah, Yaw A.; Williams, Karen; Mmieh, Frederick
<x xml:space="preserve">Abstract</x> The main aim of this article is to examine the factors that influence the inflow of financial foreign direct investment (FDI) into SSA and to understand foreign investors' perceptions of the role of institutional factors in facilitating financial FDI inflows and the extent to which the postreform business environment has been successful in attracting financial FDI inflows into SSA. An in‐depth qualitative study was adopted for the research. Using two financial multinational corporations as case studies, the environmental factors that influenced their decision to choose Ghana as an investment destination are examined, as well as the institutional and regulatory factors that affect their current operations and future investment decisions. © 2014 Wiley Periodicals, Inc.